Współpraca cenzorów z Urzędem Bezpieczeństwa i Służbą Bezpieczeństwa w Polsce w latach 1945–1989 — wybrane zagadnienia - Kamińska-Chełminiak, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The assumption of the article is to give the sense of the scope and forms of cooperation of the censorship apparatus (at the central and district level) with the Security Service in Poland in the years 1945–1989. ThisArticle has been based on archival material collected in the Archives of New Files, the Institute of National Remembrance, Archives of the Literature Institute “Culture” in Maisons-Laffitte, and Archives of the “Karta” Center in Warsaw. Also, the article consists of the memoirs of Tomasz Strzyżewski, a former employee of the Krakow delegation of GUKPPiW, obtained by the author of the text, and a censor from GUKPPiW and the office in Opole
Keywords: censorship; Security Service in Poland; Main Office for the Control of Press; Publication and Performances; Voivodeship Office for the Control of Press; Publication and Perform-ances; PRL